Cognitive Foundations for Early Mathematics Learning (Edma 0-6: Educación Matemática en la Infancia, 2021)
In this article, about cognitive foundations for early mathematics learning, we make a review of research on the learning of mathematics in the early childhood. We structure this review in the following sections: evidence for early understanding of number, development of spatial thinking and geometry, development of measurement, and regulating behavior and attention.
Keywords: Learning mathematics; Early childhood; Mathematics; Research